Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

The gender wage gap across life: Effects of genetic predisposition towards higher educational attainment - Alex Bryson; Tim Morris; David Bann; David Wilkinson (Economics & Human Biology, 2025)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Achieving conservation and restoration outcomes through ecologically beneficial aquaculture - Kathy Overton; Tim Dempster; Stephen E. Swearer; Rebecca L. Morris; Luke T. Barrett (Conservation Biology, 2024)
A range of conservation and restoration tools are needed to safeguard the structure and function of aquatic ecosystems. Aquaculture, the culturing of aquatic organisms, often contributes to the numerous stressors that aquatic ecosystems face, yet some aquaculture activities can also deliver ecological benefits. We reviewed the literature on aquaculture activities that may contribute to conservation and restoration outcomes, either by enhancing the persistence or recovery of one or more target species or by moving aquatic ecosystems toward a target state. We identified 12 ecologically beneficial outcomes achievable via aquaculture: species recovery, habitat restoration, habitat rehabilitation, habitat protection, bioremediation, assisted evolution, climate change mitigation, wild harvest replacement, coastal defense, removal of overabundant species, biological control, and ex situ conservation. This list may be expanded as new applications are discovered. Positive intentions do not guarantee positive ecological outcomes, so it is critical that potentially ecologically beneficial aquaculture activities be evaluated via clear and measurable indicators of success to reduce potential abuse by greenwashing. Unanimity on outcomes, indicators, and related terminology will bring the field of aquaculture–environment interactions into line with consensus standards in conservation and restoration ecology. Broad consensus will also aid the development of future certification schemes for ecologically beneficial aquaculture.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Dominant species of mid-elevation grasslands of the uKhahlamba-Drakensberg Park are predicted to be largely immune to climate change - Debbie Jewitt; Craig D. Morris; Tim G. O’Connor; Michelle J. Tedder (Journal of Mountain Science, 2023)

Anchor scour from shipping and the defaunation of rocky reefs: A quantitative assessment - Allison Broad; Matthew Rees; Nathan Knott; Daniel Swadling; Matthew Hammond; Tim Ingleton; Bradley Morris; Andrew R. Davis (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Multiple spatial behaviours govern social network positions in a wild ungulate - Gregory F. Albery; Alison Morris; Sean Morris; Josephine M. Pemberton; Tim H. Clutton‐Brock; Daniel H. Nussey; Josh A. Firth (Ecology Letters, 2021)
The structure of wild animal social systems depends on a complex combination of intrinsic and extrinsic drivers. Population structuring and spatial behaviour are key determinants of individuals’ observed social behaviour, but quantifying these spatial components alongside multiple other drivers remains difficult due to data scarcity and analytical complexity. We used a 43‐year dataset detailing a wild red deer population to investigate how individuals’ spatial behaviours drive social network positioning, while simultaneously assessing other potential contributing factors. Using Integrated Nested Laplace Approximation (INLA) multi‐matrix animal models, we demonstrate that social network positions are shaped by two‐dimensional landscape locations, pairwise space sharing, individual range size, and spatial and temporal variation in population density, alongside smaller but detectable impacts of a selection of individual‐level phenotypic traits. These results indicate strong, multifaceted spatiotemporal structuring in this society, emphasising the importance of considering multiple spatial components when investigating the causes and consequences of sociality.

Increased expression of plasminogen activator inhibitor-1 (PAI-1) is associated with depression and depressive phenotype in C57Bl/6J mice - René A. Girard; Prashant S. Chauhan; Torry A. Tucker; Tim Allen; Jaswinder Kaur; Ann Jeffers; Kathleen Koenig; Galina Florova; Andrey A. Komissarov; Tatiana A. Gaidenko; Mignote B. Chamiso; James Fowler; et al. (Experimental Brain Research, 2019)

Monitoring mosaic biotopes in a marine conservation zone by autonomous underwater vehicle - Noëlie M.A. Benoist; Kirsty J. Morris; Brian J. Bett; Jennifer M. Durden; Veerle A.I. Huvenne; Tim P. Le Bas; Russell B. Wynn; Suzanne J. Ware; Henry A. Ruhl (Conservation Biology, 2019)
The number of marine protected areas (MPAs) has increased dramatically in the last decade and poses a major logistic challenge for conservation practitioners in terms of spatial extent and the multiplicity of habitats and biotopes that now require assessment. Photographic assessment by autonomous underwater vehicle (AUV) enables the consistent description of multiple habitats, in our case including mosaics of rock and sediment. As a case study, we used this method to survey the Greater Haig Fras marine conservation zone (Celtic Sea, northeast Atlantic). We distinguished 7 biotopes, detected statistically significant variations in standing stocks, species density, species diversity, and faunal composition, and identified significant indicator species for each habitat. Our results demonstrate that AUV‐based photography can produce robust data for ecological research and practical marine conservation. Standardizing to a minimum number of individuals per sampling unit, rather than to a fixed seafloor area, may be a valuable means of defining an ecologically appropriate sampling unit. Although composite sampling represents a change in standard practice, other users should consider the potential benefits of this approach in conservation studies. It is broadly applicable in the marine environment and has been successfully implemented in deep‐sea conservation and environmental impact studies. Without a cost‐effective method, applicable across habitats, it will be difficult to further a coherent classification of biotopes or to routinely assess their conservation status in the rapidly expanding global extent of MPAs.

Declining home range area predicts reduced late‐life survival in two wild ungulate populations - Hannah Froy; Luca Börger; Charlotte E. Regan; Alison Morris; Sean Morris; Jill G. Pilkington; Michael J. Crawley; Tim H. Clutton‐Brock; Josephine M. Pemberton; Daniel H. Nussey (Ecology Letters, 2018)
Demographic senescence is increasingly recognised as an important force shaping the dynamics of wild vertebrate populations. However, our understanding of the processes that underpin these declines in survival and fertility in old age remains limited. Evidence for age‐related changes in foraging behaviour and habitat use is emerging from wild vertebrate studies, but the extent to which these are driven by within‐individual changes, and the consequences for fitness, remain unclear. Using longitudinal census observations collected over four decades from two long‐term individual‐based studies of unmanaged ungulates, we demonstrate consistent within‐individual declines in home range area with age in adult females. In both systems, we found that within‐individual decreases in home range area were associated with increased risk of mortality the following year. Our results provide the first evidence from the wild that age‐related changes in space use are predictive of adult mortality.

Expression of a fungal ferulic acid esterase in suspension cultures of tall fescue (Festuca arundinacea) decreases cell wall feruloylation and increases rates of cell wall digestion - Phillip Morris; Sue Dalton; Tim Langdon; Barbara Hauck; Marcia M. O. de Buanafina (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Functional co-expression of a fungal ferulic acid esterase and a β-1,4 endoxylanase in Festuca arundinacea (tall fescue) modifies post-harvest cell wall deconstruction - Marcia M. de O. Buanafina; Sue Dalton; Tim Langdon; E. Timms-Taravella; Erica A. Shearer; Phillip Morris (Planta, 2015)

Expression of a Trichoderma reesei β-1,4 endo-xylanase in tall fescue modifies cell wall structure and digestibility and elicits pathogen defence responses - Marcia M. de O. Buanafina; Tim Langdon; Sue Dalton; Phillip Morris (Planta, 2012)

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Fatty acid synthase effects on bovine adipose fat and milk fat - Chris A. Morris; Neil G. Cullen; Belinda C. Glass; Dianne L. Hyndman; Tim R. Manley; Sharon M. Hickey; John C. McEwan; Wayne S. Pitchford; Cynthia D.K. Bottema; Michael A.H. Lee (Mammalian Genome, 2007)